Students ́ Satisfaction in EMI Courses: Fostering Entrepreneurial Language Skills - Gonzales, Iris; Baleriano, Yenifer; Valdez, Denise (LACCEI, 2025)
This quantitative research primarily evaluates university student satisfaction with English Medium Instruction (EMI) courses, encompassing both their academic programs and entrepreneurship classes, in two pioneering Honduran private universities. Within their initial 18 months of EMI implementation, these institutions have notably advanced educational transformation and fostered entrepreneurial skill development, aiming to enhance global opportunities for students. A probability model results indicate that pedagogical, affective, and entrepreneurial dimensions significantly and positively correlate with students' likelihood of recommending EMI courses. Conversely, the study found no statistical significance for linguistic-communicative and virtual classroom dimensions, suggesting an adequate student linguistic base or successful adaptation to online learning environments for the surveyed population. This research identifies ongoing challenges, particularly in motivating increased teacher participation and accurately measuring students' language proficiency within EMI contexts. The findings offer an empirical foundation for refining EMI strategies through enhanced teaching quality, positive learning environments, and integrated entrepreneurial skill development. Future research could further explore student preference heterogeneity using qualitative or longitudinal designs and conduct comparative analyses with other university contexts.